Prolonged activity and toxicity of sirolimus in a patient with metastatic renal perivascular epithelioid cell tumor: a case report and literature review. Issue 6 (July 2018) - Raimondi, Alessandra; Colombo, Francesca; Pintarelli, Giulia; Morosi, Carlo; Renne, Salvatore L.; Frezza, Anna M.; Saponara, Maristella; Dei Tos, Angelo P.; Mazzocchi, Arabella; Provenzano, Salvatore; Casali, Paolo G.; Stacchiotti, Silvia
Abstract : Perivascular epithelioid cell tumor (PEComa) is a family of mesenchymal tumors. Conventional chemotherapy has little activity in this disease, but case reports are available on the activity of mammalian target of rapamycin inhibitors (e.g. sirolimus and temsirolimus). Pharmacokinetic assays of sirolimus are available as this drug has a precise therapeutic window and blood levels might be influenced by CYP3A4 polymorphisms and drug interactions. We report on a case of a patient with metastatic, progressive PEComa who started sirolimus at a dose of 5 mg/day with evidence of grade (G) 3 mucositis, G2 thrombocytopenia, and G1 leucopenia 10 days after the treatment started, in absence of concomitant medications or prohibited food assumption. Elevated sirolimus blood levels were detected (156.8 ng/ml). Sirolimus was stopped, and toxicity resolved in 5 weeks. Computed tomography scan 2 months after the treatment started showed a partial response (RECIST). After toxicity resolution, the patient restarted sirolimus at a dose of 1 mg/day, with blood levels in the range of 10–20 ng/ml. Tumor response was confirmed and maintained, and the patient is still under treatment 18 months later, with no additional adverse effects. Genetic analysis of five selected polymorphisms (rs2740574, rs776746, rs1128503, rs2032582, and rs1045642) in drug metabolism enzymes and transporters did not provide a clear explanation of the observed unusual pharmacokinetic. This case confirms the activity of mammalian target of rapamycin inhibitors in PEComa and strengthens the importance of pharmacokinetic drug blood levels monitoring in patients treated with sirolimus. In our patient, after dose adjustment, sirolimus could be restarted with a prolonged clinical benefit and no additional toxicity.